Anti-inflammatory and analgesic activity of leaf and callus extracts of Coleus forskohlii - Sunitha Kundur; Prathap Reddy Karnati; Manohar Rao Daggu (International Journal of Phytomedicine, 2012)
Though all sixteen combinations of NAA + BAP, and NAA + KN induced callus from leaf explants of Coleus forskohlii with a variable response, 0.5 mg/l NAA + 1.5 mg/l BAP was the most efficient (100%) followed by 1.0 mg/l NAA + 2.5 mg/l KN (86%). Investigations were made for anti-inflammatory and analgesic activity of hydroalcoholic extracts of leaf and callus on Swiss albino mice. Anti-inflammatory studies were performed by Carrageenan induced paw edema (acute) and Cotton pellet induced granuloma (chronic) models, while the analgesic activity was tested by: glacial acetic acid induced writhing and tail immersion models. Maximum anti-inflammatory activity was exhibited by 200 mg/kg callus extract (43% in acute and 22.3% in chronic) followed by 200 mg/kg leaf extract (37% in acute and 21.8% in chronic) compared to standard drug, the aspirin (27.4% in acute and 29.9% in chronic). In writhing model, 200 mg/kg callus extract exhibited highly significant (p < 0.01) reduction in writhing count compared to 200 mg/kg (p < 0.01) leaf extract. In tail immersion model also the reaction time was significantly reduced (p < 0.01) by both callus and leaf extracts throughout observation period of 3 hrs. The results obtained supported the use of this plant in traditional medicine.